A comparison of foam rolling and vibration foam rolling on the quadriceps muscle function and mechanical properties - Reiner, Marina Maren (Eur J Appl Physiol, 2021)
PURPOSE: The purpose of the study was to investigate the effects of using a vibration foam roll (VFR) or a non-vibration foam roll (NVFR) on maximum voluntary isometric contraction peak torque (MVIC), range of motion (ROM), passive resistive torque (PRT), and shear modulus. METHODS: Twenty-one male volunteers visited the laboratory on two separate days and were randomly assigned to either a VFR group or a NVFR group. Both interventions were performed for 3 × 1 min each. Before and after each intervention, passive resistive torque and maximum voluntary isometric contraction peak torque of the leg extensors were assessed with a dynamometer. Hip extension ROM was assessed using a modified Thomas test with 3D-motion caption. Muscle shear modulus of the vastus lateralis (VL), vastus medialis (VM), and rectus femoris (RF) was assessed with shear wave elastography (SWE). RESULTS: In both groups (VFR, NVFR) we observed an increase in MVIC peak torque (+ 14.2 Nm, + 8.6 Nm) and a decrease in shear modulus of the RF (− 7.2 kPa, − 4.7 kPa). However, an increase in hip extension ROM (3.3°) was only observed in the VFR group. There was no change in PRT and shear modulus of the VL and VM, in both the VFR group and the NVFR group. Our findings demonstrate a muscle-specific acute decrease in passive RF stiffness after VFR and NVFR, with an effect on joint flexibility found only after VFR. CONCLUSION: The findings of this study suggest that VFR might be a more efficient approach to maximize performance in sports with flexibility demands.